Does diabetes affect the intensity of staining of interstitial cells and neuronal tissue in the bladder, prostate and urethra of rabbits - Canda, Abdullah Erdem; Aktas, Safiye; Turna, Burak; Cinar, Mehtap G (Central European journal of medicine, 2010)
We compared the intensity of staining of interstitial cells (ICs) and neural tissue in the lower urinary tract of rabbits with diabetes with the intensity in normal subjects. Diabetes was induced by injecting alloxane (65mg/kg) in adult male rabbits. After 3 days, rabbits with a blood glucose level >300 mg/dL were considered to have diabetes. After 8 weeks, the rabbits were killed, and tissue specimens from the bladder, prostate and urethra were obtained. ICs were stained with anti-human CD117 (c-kit) rabbit polyclonal antibody, and neural tissue was stained with synaptophysin. The streptavidin-biotin method was used for immunohistochemical staining. The intensity of c-kit and synaptophysin staining were scored as negative (0), weak (+), moderate (++), and strong (+++). Staining intensity of ICs and neural tissue was assessed and compared in tissues obtained from rabbits with diabetes (n=8) and from control subjects (n=7). Although staining intensity of both ICs and neural tissue was found to be significantly decreased in the bladder tissue of rabbits with diabetes compared to that in the control group (p=0.0001 [ICs] and p=0.021 [neural tissue]), no significant differences in staining intensity of ICs and neural tissue in the urethra and in the prostate was found when rabbits with diabetes were compared to the control group. Diabetes may cause dysfunction of the lower urinary tract, particularly in the urinary bladder, as shown by the staining intensity of ICs and neural tissue.